2020
DOI: 10.3390/cells9051307
|View full text |Cite
|
Sign up to set email alerts
|

Joint Reconstituted Signaling of the IL-6 Receptor via Extracellular Vesicles

Abstract: Interleukin-6 (IL-6) signaling is a crucial regulatory event important for many biological functions, such as inflammation and tissue regeneration. Accordingly, several pathological conditions are associated with dysregulated IL-6 activity, making it an attractive therapeutic target. For instance, blockade of IL-6 or its α-receptor (IL-6R) by monoclonal antibodies has been successfully used to treat rheumatoid arthritis. However, based on different signaling modes, IL-6 function varies between pro- and anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…Another effect that is often seen in condition where a sheddase is missing, is the release of proteolytic substrates on extracellular vesicles. This was shown for the ADAM10 substrate prion protein (Linsenmeier et al, 2018), the ADAM10/ADAM17 and meprin β substrate IL-6R (Arnold et al, 2020) and the meprin β substrate CD109 (Luckstadt et al, 2021). Whether this effect holds true for CD44 and has any biological effect on cells, has to be elucidated in future research projects.…”
Section: Discussionmentioning
confidence: 88%
“…Another effect that is often seen in condition where a sheddase is missing, is the release of proteolytic substrates on extracellular vesicles. This was shown for the ADAM10 substrate prion protein (Linsenmeier et al, 2018), the ADAM10/ADAM17 and meprin β substrate IL-6R (Arnold et al, 2020) and the meprin β substrate CD109 (Luckstadt et al, 2021). Whether this effect holds true for CD44 and has any biological effect on cells, has to be elucidated in future research projects.…”
Section: Discussionmentioning
confidence: 88%
“…It was previously demonstrated that CD109 can be sorted onto EVs ( Sakakura et al, 2016 ; Yamamoto et al, 2019 ), and here we can show that proteolytic activity at the cell surface reduces this CD109 secretion mechanism. It was shown previously for the IL-6 receptor ( Arnold et al, 2020 ) and the Prion protein ( Linsenmeier et al, 2018 ) that proteolytic activity controls the amount of membrane proteins sorted onto EVs. The vesicular morphology was, however, unchanged when comparing CD109 containing or non-containing vesicles, unlike for the release of PRDX4, where larger vesicles were detected ( Lipinski et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For extracellular measurements in negative staining transmission electron microscopy (TEM) or for dynamic light scattering analysis (DLS), samples must be free from any matrix as it would be found in the abovementioned isolation kit. Therefore, EVs were isolated using ultracentrifugation as described previously ( Arnold et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In classical signalling, IL-6 has regenerative and anti-inflammatory functions, which are enacted through STAT3 activation of the signalling pathway via the surface IL-6 receptor [ 36 ]. However, for an anti-inflammatory function, a trans-signalling processes is achieved via a soluble receptor gp130 [ 37 ] or through active IL-6 uptake linked to EV packaging and translocation in cells that lack an IL-6 receptor [ 38 ]. In this study, the IL-6 thigh ADSC EV content ratio was substantially higher than that in abdomen ADSCs and chin ADSCs.…”
Section: Discussionmentioning
confidence: 99%